Lipid metabolism in ferroptosis and ferroptosis-based cancer therapy - Sun, Yonghao; Xue, Zuoxing; Huang, Tao; Che, Xiangyu; Wu, Guangzhen (Frontiers in Oncology, 2022)
Ferroptosis refers to iron-dependent, specialized, and regulated-necrosis mediated by lipid peroxidation, which is closely related to a variety of diseases, including cancer. Tumor cells undergo extensive changes in lipid metabolism, including lipid peroxidation and ferroptosis. Changes in lipid metabolism are critical for the regulation of ferroptosis and thus have important roles in cancer therapy. In this review, we introduce the characteristics of ferroptosis and briefly analyze the links between several metabolic mechanisms and ferroptosis. The effects of lipid peroxides, several signaling pathways, and the molecules and pathways involved in lipid metabolism on ferroptosis were extensively analyzed. Finally, our review highlights some ferroptosis-based treatments and presents some methods and examples of how these treatments can be combined with other treatments.